Menguak Alasan Dibalik Minimnya Nasabah Pengguna Bank Syariah Di Gorontalo - Mirzan Gulam (AKASYAH: Jurnal Akuntansi, Keuangan dan Audit Syariah, 2021)
In Gorontalo, Islamic Banking has the same potential as other financial institutions. But the number of customers saving at a Sharia Bank will still be very minimal and this is certainly in contrast to the majority of Gorontalo Muslims who are Muslim. The reason is there are several things such as the lack of public knowledge about the principles and concepts of Islamic Banks and service systems in Islamic Banks that are not as modern and as good as Conventional Banks, as well as the lack of branch offices or units that are scattered in Gorontalo. This prompted researchers to examine the causes of the lack of customers using Islamic banks as well as the factors that caused underdeveloped Islamic banks in Gorontalo. In this study, researchers used qualitative methods, namely using secondary data types and using four data collection techniques, namely, documentation, literature studies, discussions / interviews, and intuitive-subjective. The results of this study indicate that the importance of the role of Islamic Banks for the majority of Gorontalo people is Muslim so that it requires an increase.